Pengaruh Pendidikan Kewirausahaan,Lingkungan Keluarga, Motivasi Berwirausaha Terhadap Minat Berwirausaha - Erren Setyaki; Sugiyanto Sugiyanto (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study examines and analyzes the effect of Entrepreneurship Education, Family Environment, Entrepreneurial Motivation simultaneously and partially on Interest in Entrepreneurship in Active Students of the Faculty of Economics and Business, University of Esa Unggul. The research approach used in this research is quantitative research. The criteria for selecting the sample in this study were those aged 17 and over who had been and were interested in entrepreneurship. Questionnaires collected as many as 150 respondents, the data is then processed using multiple linear regression method. Based on the results of the analysis it is known that the variables of Entrepreneurship Education, Family Environment, Entrepreneurial Motivation simultaneously have a positive effect on Entrepreneurial Interest in active students of the Faculty of Economics and Business, University of Esa Unggul. Partially the variable Family Environment, Entrepreneurial Motivation has a positive effect on Interest in Entrepreneurship in students of the Faculty of Economics and Business, University of Esa Unggul. Partially, Entrepreneurship Education has a negative effect on Interest in Entrepreneurship.